1991
DOI: 10.1002/1097-0142(19910215)67:4<984::aid-cncr2820670421>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistologic evaluation of parathyroid hormone-related protein in human lung cancer and normal tissue with newly developed monoclonal antibody

Abstract: With a newly developed monoclonal anti-PTHrP antibody, 4B3, the immunohistochemical localization of the parathyroid hormone-related protein (PTHrP) was studied on the formalin-fixed and paraffin-embedded sections of normal human tissues and various subtypes of lung cancer. Among normal epithelial tissues, keratinocytes in squamous epithelia, transitional and bronchial epithelia with squamous metaplasia, meningoepithelial cells, and mammary ductal cells with lactating changes showed positive immunoreactivity. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(40 citation statements)
references
References 12 publications
5
34
1
Order By: Relevance
“…Human foetal lung is a plentiful source of PTHrP [S], as are many cases of carcinoma of the lung [4]. In contrast, nom?nl adult human lung does not appear to express the peptide.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Human foetal lung is a plentiful source of PTHrP [S], as are many cases of carcinoma of the lung [4]. In contrast, nom?nl adult human lung does not appear to express the peptide.…”
supporting
confidence: 91%
“…Expression of PTHrP is not confined to tumour cells, having been isolated in a variety of normal human adult [4] and foetal tissues . The role it plays in adult physiology is unclear but in the case of the foetus it has been suggested that PTI-IrP may be responsible for the maintenance of the foetus-directed transplacental calcium gradient [S] and, additionally it may play a role as a foetal growth factor ['?I.…”
Section: Introductionmentioning
confidence: 99%
“…PTHrP acts as an autocrine, paracrine, or intracrine factor in a wide range of developmental and physiological processes (7,8), it has growth-promoting and antiapoptotic properties (6), and it plays a crucial role in the development of the mammary gland and skeleton (8)(9)(10). Of special interest is the association of PTHrP with oncologic pathologies such as breast cancer (11,12) and lung (13)(14)(15), prostate (16)(17)(18), renal (19), colorectal (20)(21)(22), skin (23,24), and gastric carcinomas (25,26). Circulating levels of PTHrP generally correlate with the more advanced stages of cancer (20,(27)(28)(29)(30)(31)(32), and PTHrP regulates the expression of several tumor-relevant genes (33).…”
Section: Introductionmentioning
confidence: 99%
“…PTHrP has been isolated as a major factor responsible for HHM 12 and is known to be produced by various types of tumors. [13][14][15][16] Therefore, serological analysis of PTHrP might be useful in determining the cause of hypercalcemia in patients with malignant tumors. In the present case there was an extremely high preoperative serum concentration of C-PTHrP, which normalized immediately after the surgery, as did the elevated serum calcium concentration.…”
Section: Discussionmentioning
confidence: 99%